DIFFICULTY IN PRONUNCIATION OF DIPHTHONGS AMONG PUBLIC SECONDARY SCHOOL STUDENTS IN ANAMBRA STATE - Ogechukwu Mary Nwanna (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2024)
The study examined the difficulties students encountered in pronouncing diphthongs. Specifically, the study highlighted some areas that posed problems for students in articulating diphthong sounds. The study was anchored in language acquisition theory, which posited that learners have acquired a first language and that their L1 might hamper the articulation of sounds, and in error analysis theory, which stated that a learner’s errors reflect their learning process. Here, the errors an L2 learner makes are traceable to either intra-lingual or developmental in nature or inter–lingual (transfer). A descriptive research design was adopted to describe the areas students find difficult when pronouncing diphthongs. Data were collected through structured questionnaires. Data were equally analyzed using mean scores. The study's findings revealed that ignoring glides in pronunciation and overemphasizing the first vowel were among the problematic areas that students couldn’t articulate properly. The study concluded that students should be exposed to continuous drilling to improve their pronunciation skills. This is because a second language learner has not gained veritable knowledge of how these diphthongs are pronounced. It was recommended, amongst others, that teachers attend workshops on the training prevalent in these diphthongs and possibly teach the students more effectively.